Mobile bullying in South Africa – exploring its nature, influencing factors and implications - Oosterwyk, Grant Wayne (Department of Information Systems, 2014)
Mobile bullying is a form of electronic bullying that is relatively new. It involves the use of mobile technology applications such as email, chat rooms, instant messaging and small text messages. This form of bullying often goes unnoticed. Victims, institutions and parents are unaware of how to deal with it and there is limited knowledge about its legal and social implications. Due to an increase in mobile web adoption as well as active mobile users in South Africa, mobile bullying is escalating and has become a major concern in schools and communities. There is limited empirical research examining this type of aggression in schools. We lack knowledge of the nature and prevalence in schools and there are no effective models to predict or measure the level of this aggression. The present study aims to bridge this gap by examining the nature, prevalence and implications of this form of aggression in various South African high schools. The study will also identify the significant factors influencing this aggression and aims to create awareness of the problem.